The State of Women and Women’s Education at the Beginning of Tokugawa Shogunate (1603-1651) - Riza Afita Surya; Teresa Angelina Kaluge (IZUMI, 2021)
This study attempted to draw a more critical analysis of women and their education at the beginning of the Tokugawa period. Tokugawa, or the Edo period in Japan, was a warrior society. It is one of the most studied fields for many scholars as it highlighted the feature of Japanese culture until today. In Japan, women’s studies began in the 1970s, which is considered late than Western. Recently, there is still limited research regarding women’s education activities being conducted under the Tokugawa shogunate. This study engaged historical methods, namely heuristics, criticism, interpretation, and historiography. At the beginning of the Tokugawa era, women’s education was varied based on social status and families’ occupation. The gap of education between men and women and noblewomen and commoners is a mystifying matter as some historical accounts address the contrary facts. Many historical writings indicate that women at the beginning of the Tokugawa period experienced great repression and hierarchical subjugation. However, several accounts addressing the role of women during Tokugawa were relatively better as women received fitted and suitable education during the period. Therefore, it is necessary to identify Tokugawa’s social and political context more closely than making the judgment based on how it used to be since many classical historiographies in the past solely focus on the ruling class. Finally, the time needed for education equality toward women in Japan indicating that education was important for the whole population that would need to be given to all.